Reduced material loss in thin-film lithium niobate waveguides - Amirhassan Shams-Ansari; Guanhao Huang; Lingyan He; Zihan Li; Jeffrey Holzgrafe; Marc Jankowski; Mikhail Churaev; Prashanta Kharel; Rebecca Cheng; Di Zhu; Neil Sinclair; Boris Desiatov; et al. (APL Photonics, 2022)
Thin-film lithium niobate has shown promise for scalable applications ranging from single-photon sources to high-bandwidth data communication systems. Realization of the next generation high-performance classical and quantum devices, however, requires much lower optical losses than the current state of the art resonator (Q-factor of ∼10 million). Yet the material limitations of ion-sliced thin film lithium niobate have not been explored; therefore, it is unclear how high the quality factor can be achieved in this platform. Here, using our newly developed characterization method, we find out that the material limited quality factor of thin film lithium niobate photonic platform can be improved using post-fabrication annealing and can be as high as Q ≈ 1.6 × 108 at telecommunication wavelengths, corresponding to a propagation loss of 0.2  dB/m.